2008
DOI: 10.1002/adfm.200800653
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optoelectronic Properties of Nonpolar Polyrotaxane Insulated Molecular Wires with High Solubility in Organic Solvents

Abstract: Hydrophilic polyanionic conjugated polyrotaxanes are readily synthesized in water by Suzuki coupling, but their high polarity and ionic nature limit the potential applications of these materials. Here, we demonstrate three methods for transforming these polar polyelectrolytes into nonpolar lipophilic insulated molecular wires. A water‐soluble polyfluorene‐alt‐biphenylene β‐cyclodextrin (CD) polyrotaxane was converted into nonpolar derivatives by methylation of the carboxylic acid groups with diazomethane and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 42 publications
5
46
0
Order By: Relevance
“…The positive band in both cases is attributed to the stimulated emission (SE), which spectral position matches with the photoluminescence spectra of the polymers [3]. The negative part of the spectrum for the neat polymer shows two well pronounced minima.…”
Section: Figuresupporting
confidence: 64%
“…The positive band in both cases is attributed to the stimulated emission (SE), which spectral position matches with the photoluminescence spectra of the polymers [3]. The negative part of the spectrum for the neat polymer shows two well pronounced minima.…”
Section: Figuresupporting
confidence: 64%
“…The same colour scheme applies to the whole figure. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Importantly, the functionalization with the polar side chains does not interfere with the conjugated π-orbitals of the polyfluorene backbone and thus leads to no modification in the position of the HOMO and LUMO levels 57,58 . As a result, all polymers exhibit comparable absorption spectrum typical of polyfluorenes 28 , with low energy absorption band at approximately 395 nm 56,58 , as shown in Fig.1g together with the optical properties of the CdSe/CdS DiRs.…”
mentioning
confidence: 97%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Importantly, the functionalization with the polar side chains does not interfere with the conjugated π-orbitals of the polyfluorene backbone and thus leads to no modification in the position of the HOMO and LUMO levels 57,58 . As a result, all polymers exhibit comparable absorption spectrum typical of polyfluorenes 28 , with low energy absorption band at approximately 395 nm 56,58 , as shown in Fig.1g together with the optical properties of the CdSe/CdS DiRs. In these heterostructures, similar to zero-and bi-dimensional core/shell CdSe/CdS systems 59 , the large (400 meV) energy offset between the CdSe and CdS valence bands along with the essential alignment of the conduction band energy ( Fig.1d) leads to the formation of a quasi type II heterojunction 49 where the hole wave function is localised inside the CdSe dot while the electron wave function spreads over the rod region within the attractive Coulomb potential of the hole.…”
mentioning
confidence: 97%
“…This encapsulation can lead to desirable properties such as enhanced environmental stability and increased photoluminescence (PL) and electroluminescence efficiencies. Anderson et al [36] have demonstrated that silylation, alkylation, and esterification of water-soluble polyrotaxane IMWs can give materials with modified organic solubility and enhanced backbone insulation. The properties of the lipophilic polyrotaxanes reflect an increased level of backbone insulation, and enhanced PL efficiency.…”
Section: Protecting Dyes and Insulating Molecular Wiresmentioning
confidence: 99%